1982
DOI: 10.1002/ajmg.1320120207
|View full text |Cite
|
Sign up to set email alerts
|

The role of Yp in sex determination: New evidence from X/Y translocations

Abstract: A 33-year-old man had azoospermia and tubular atrophy as in the Klinefelter syndrome but short stature. He had a 46,X,t(X/Y) (Xqter lead to p22.3::Yp11 lead to Yqter) translocation and was H-Y antigen-positive. This excludes one of the genes controlling H-Y antigen from the terminal portion of the short arm of the Y chromosome. This case and the two similar ones in the literature indicate that the proximal Yp portion is required for the differentiation of a male gonad. The pattern of X inactivation was random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
(2 reference statements)
2
15
0
1
Order By: Relevance
“…However, his first cousin, also affected by the same chromosomal abnormality, was below the 3rd centile for height when observed at age 6 yr and 6 mo. SS has been described in the original reports of cases 1 (20), 11 (12), 15 (19), and 16 (14). In patients 2, 6, and 9 the height was 131, 65, and 108 cm at age 13 yr (<3rd centile), 8 mo (12).…”
mentioning
confidence: 91%
“…However, his first cousin, also affected by the same chromosomal abnormality, was below the 3rd centile for height when observed at age 6 yr and 6 mo. SS has been described in the original reports of cases 1 (20), 11 (12), 15 (19), and 16 (14). In patients 2, 6, and 9 the height was 131, 65, and 108 cm at age 13 yr (<3rd centile), 8 mo (12).…”
mentioning
confidence: 91%
“…Since X-linked ichthyosis is due to steroid sulfatase deficiency, it is probable that ichthyosis would have occurred, had he survived. Steroid sulfatase activity was examined in six familial cases, including our case (Speevak et aI., 1985;Ross et al, 1985;Boyd et al, 1981;Metaxotou et at., 1983;Tiepolo et at., 1980) and one sporadic case (Zuffardi et al, 1982). Among these cases, steroid sulfatase activity in female carriers except for those reported by Speevak et al (1985) showed a value half that of normal females, and was almost zero in male patients.…”
Section: Discussionmentioning
confidence: 80%
“…Among those reported in the literature, four phenotypic male patients having a normal X chromosome are included. Although the karyotype of the patient reported by Bernstein et al (1978) was stated to be 46,X,t(X;Y)(p22;ql 1), it is possible that it could be reinterpreted to have been Yp (Zuffardi et al, 1982). In other two cases (Bernstein et al, 1980;Zuffardi et at., 1982), Yp was contained in the X;Y translocation chromosome.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Esta parece ser la unica funcion genetica del cromosoma Y, ya que la diferenciacion mascultna se efectua bajo la influencia de androgenos secretados por los testi'culos 9 . Si solo existe Yq, los pacientes son de sexo femenino y la translocacion puede ser trasmitida a hijos hombres o mujeres 6 . El mosaicismo consiste en la presencia simul- tanea de dos o mas h'neas celulares diferentes en un individuo.…”
Section: Discusionunclassified